Doctoral Dissertations in the Internet: A Good Start in Finland - Häkli, Esko; Lehtinen, Henna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
At the present stage of the IT-applications the change from print publishing into electronic publishing of doctoral dissertations is not only a question of technology but it is also, and possibly even to a greater extent, a question of thinking. Although there is a large selection of technologies and publication formats available, none of them seem to be mature enough to be a self-evident choice. But obviously a greater obstacle can be found in the minds of people. In many cases legal regulations also have to be revised. Academic traditions still prefer properly printed dissertations and the attitudes of the academic community are not necessarily favourable towards electronic publishing in general. Young post-graduate students are obviously not able to appreciate a virtual dissertation. They seem to need a real tangible thing, which they also can show to their parents! And finally, the whole organization and financing of publishing may need to be revised, an exercise which is far more difficult than only starting to use new technology.